La defensa de la especificidad española frente al advenimiento de la cultura liberal (1833-1839) - Laetitia Blanchard Rubio (Cahiers de Civilisation Espagnole Contemporaine)
The First Carlist Civil War represents the confrontation of the two main government principles based on opposite ways of understanding the notion of civilization. The Carlists condemn the devastating effects of a new universalist culture and present Spain as a country protected from this new « illness » affecting other European countries. The changes required by the Spanish liberals involve the Carlists' praise of a Basque culture built up in contradiction with the concept of a cosmopolitan culture presented by Madrid. According to the defenders of carlism, these exemplary Spaniards fight to safeguard the kind of culture they wish could spread not only through Spain but also through every European country. In order to reach this goal, they put forward an idealized vision of the Basques. This representation of a primitive people, very similar to the Myth of the Golden Era or the natural state theorized by Rousseau, can be found not only in carlist political propaganda, but also in the works of several liberal whose interest in the habits and customs of a society about to lose its values and references comes from their romantic culture.